2002
DOI: 10.1016/s1470-0328(02)01212-0
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture treatment during labour—a randomised controlled trial

Abstract: The results suggest that acupuncture could be a good alternative or complement to those parturients who seek an alternative to pharmacological analgesia in childbirth. Further trials with a larger number of patients are required to clarify if the main effect of acupuncture during labour is analgesic or relaxing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 10 publications
2
53
1
2
Order By: Relevance
“…15 Participants and settings A total of 2038 participants were involved, ranging from 90 to 607 per study. Four studies recruited only nulliparous women; [16][17][18][19] five studies had both nulliparous and multiparous women; 15,[20][21][22][23] and parity was not mentioned in one study. 24 The majority of the studies included women at more than 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Participants and settings A total of 2038 participants were involved, ranging from 90 to 607 per study. Four studies recruited only nulliparous women; [16][17][18][19] five studies had both nulliparous and multiparous women; 15,[20][21][22][23] and parity was not mentioned in one study. 24 The majority of the studies included women at more than 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…A range of comparison groups were used including transcutaneous electrical nerve stimulation (TENS), 18,20 conventional analgesia, 20,22,23 minimal acupuncture at nonacupoints, 15,19,24 EDA, 18 subcutaneous sterile water injection, 21 placebo EA, 16,17 and no intervention. [16][17][18]24 Two studies 16,17 from China employed placebo EA where needle penetrating was simulated, followed by needle fixing on an acupoint with adhesive tapes and connected to an inactive electric device.…”
Section: Types Of Control Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acupuncture seems to help women manage labour pain and avoid pharmacological pain relief, though it is still unclear if acupuncture can reduce pain intensity [2,3]. Some studies have found that acupuncture leads to a reduction of pain during labour [4,5], whereas other studies have not [6][7][8][9]. Three studies, however, reported that acupuncture leads to a reduced use of pharmacological pain relief such as epidural analgesia and pethidin [6,7,10].…”
Section: Introductionmentioning
confidence: 99%